Earth Imaging From the Surface of the Moon With a DSCOVR/EPIC-Type Camera - Gorkavyi, Nick; Carn, Simon; DeLand, Matt; Knyazikhin, Yuri; Krotkov, Nick; Marshak, Alexander; Myneni, Ranga; Vasilkov, Alexander (Frontiers in Remote Sensing, 2021)
The Earth Polychromatic Imaging Camera (EPIC) on the Deep Space Climate Observatory (DSCOVR) satellite observes the entire Sun-illuminated Earth from sunrise to sunset from the L1 Sun-Earth Lagrange point. The L1 location, however, confines the observed phase angles to ∼2°–12°, a nearly backscattering direction, precluding any information on the bidirectional surface reflectance factor (BRF) or cloud/aerosol phase function. Deploying an analog of EPIC on the Moon’s surface would offer a unique opportunity to image the full range of Earth phases, including observing ocean/cloud glint reflection for different phase angles; monitoring of transient volcanic clouds; detection of circum-polar mesospheric and stratospheric clouds; estimating the surface BRF and full phase-angle integrated albedo; and monitoring of vegetation characteristics for different phase angles.